Some Psychometric Properties of the Brazilian CDC Clear Communication Index - Angélica Maria Cupertino Lopes Marinho; Cynthia Baur; Lucas Emanuel Oliveira Costa; Juliana Vaz de Melo Mambrini; Fernanda Morais Ferreira; Ana Cristina Borges-Oliveira; Mauro Henrique Nogueira Guimarães de Abreu (SLACK Incorporated, 2022)
The Centers for Disease Control and Prevention (CDC) Clear Communication Index (CCI) was cross-culturally adapted to Brazilian Portuguese (BR). It was necessary to analyze the reliability and validity of the BR-CDC-CCI for its use in Brazil. This study aimed to evaluate the psychometric properties of the instrument in its Brazilian version. Four specialists in health education used the BR-CDC-CCI to evaluate a population-level health education material. Primary health care professionals (n = 105) evaluated the same health material using the BRCDC-CCI, and 30 professionals performed the retest 15 to 20 days after the first assessment. Cohen Kappa and area under the receiver operating characteristic (ROC) curve analyses were developed. Inter-rater agreement ranged from moderate to almost perfect, with 90% of the items almost perfect. The percentage of agreement ranged from 8.6% to 98.1%. For the analyzed questions, the area on the ROC curve was 0.9412 (confidence interval [CI] 95%; [0.8259, 1.000]). The BR-CDC-CCI had sufficient validity and reliability for its use in the evaluation of educational/informational materials in health in the Brazilian context. In view of the good results from this psychometric assessment, we anticipated the BR-CDC-CCI could contribute to improvements in Brazilian professionals' skills in developing health communication materials, thereby improving the quality of education and, possibly health outcomes. [HLRP: Health Literacy Research and Practice. 2022;6(2):e84-e87.]